Moralitas Berpacaran di Kalangan Remaja: Studi Penelitian di SMA 1 Mandrehe - Paulinus Kanisius Ndoa; Elisabeth Cahaya Ceria Hia (STP Dian Mandala Gunungsitoli Nias Keuskupan Sibolga, 2024)
Adolescence is the period of puberty. Children experience growth and development especially in friendship. This friendship leads to feelings of liking for the opposite sex which is called courtship. Dating in the sense of special friendship between young men and women in principle has a good purpose to get to know each other's personalities. But this good intention is sometimes tainted by the irregularities that occur in the courtship process. This deviation occurs because of the wrong concept of dating as well as the moral decline among teenagers. This study uses a qualitative approach with the aim of knowing the morality of dating among adolescents at SMA Negeri I Mandrehe. The research findings are as follows: In general, respondents have received education and assistance from teachers and parents about how to interpret courtship. Even so, some of them have not interpreted courtship precisely. In fact, some of them had bad experiences in dating. Some of them openly share their dating experiences with their parents.